2016
DOI: 10.1007/s12072-016-9724-7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus cell entry: a target for novel antiviral strategies to address limitations of direct acting antivirals

Abstract: Hepatitis C virus (HCV) infection remains a major global health problem, with 130-170 million chronically infected individuals at risk to develop severe liver disease, including hepatocellular carcinoma. Although the development of direct-acting antivirals offers cure for a large majority of patients, there are still a number of clinical challenges. These include DAA failure in a significant subset of patients, difficult-to-treat genotypes and limited access to therapy due to high costs. Moreover, recent data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 102 publications
(115 reference statements)
1
30
0
Order By: Relevance
“…Almost 2.5%of the chronic HCV cases leads to HCC and the underlying virus-associated mechanisms is complex comprising both the host and viral factors where host-virus interactions lead to robust T-cell immune response elicitation (Colpitts & Baumert, 2016; Farazi & DePinho, 2006). …”
Section: Causes For Hepatocellular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Almost 2.5%of the chronic HCV cases leads to HCC and the underlying virus-associated mechanisms is complex comprising both the host and viral factors where host-virus interactions lead to robust T-cell immune response elicitation (Colpitts & Baumert, 2016; Farazi & DePinho, 2006). …”
Section: Causes For Hepatocellular Carcinomamentioning
confidence: 99%
“…As a result, early diagnosis is crucial for successful treatment. Computed tomography (CT), magnetic resonance imaging (MRI), ultrasound and dynamic multiphasic multi-detector-row CT (MDCT) are the standard HCC diagnostic methods (Bertino et al, 2014; Daoudaki & Fouzas, 2014). Based on the tumor size, serum albumin, bilirubin and α-fetoprotein (AFP) levels, HCC morphology, presence of portal vein thrombosis and ascites, various classifications are used in order to categorize the stage of the disease, particularly Okuda staging system (I-III), Cancer of Liver Italian Program (CLIP) score (0-6), Barcelona Clinic Liver Cancer (BCLC) (Table 1), American Association for the Study of the Liver Disease (AASLD), National Comprehensive Cancer Network (NCCN) and European Association for the Study of the Liver (EASL) are noteworthy (Bertino et al, 2014; Trojan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…An antibody against Claudin-1 can control HCV in human liver chimeric mice [205]. It is possible that these entry inhibitors will have a role in future HCV therapy [206].…”
Section: Hcv Co-receptorsmentioning
confidence: 99%
“…These independent studies identified several structurally related compounds as potent HCV cell entry inhibitors both in vitro and in vivo. HCV cell entry is a complex process that involves multiple entry factors, among which the scavenger receptor class B type 1 (SR-B1), the tetraspanin CD81, and the tight junction proteins claudin-1 (CLDN1) and occludin (OCLN) are absolutely required (8,9). HCV is taken up, through clathrinmediated endocytosis, into host cells (10,11), where the viral glycoproteins E1 and E2 coordinate viral membrane fusion in a process that is triggered by the low pH in endosomes (12) (Fig.…”
Section: Ion Channel Inhibitors and Related Antihistamines As First-imentioning
confidence: 99%